2020
DOI: 10.22219/jrak.v10i1.10539
|View full text |Cite
|
Sign up to set email alerts
|

How Banking Stock Prices Respond to Gross Domestic Product, Exchange Rates and Inflation: Empirical Studies of Indonesia and Hong Kong

Abstract: The study aims to analyze how banking stock prices response to GDP, inflation and exchange rate in the Indonesia Stock Exchange (IDX) and Hong Kong Stock Exchange (HKEX). For this purpose a panel data of of seven listed bank’s company in each country for the 2016Q1-2018Q4 period is used for empirical analysis.  The model analysis using static and dynamic panel regression.  Static regression used are Fixed Effect, Random Effect or Common Effect by Chow test while dynamic regression used Generalized Method of Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
2
6
3
3
Order By: Relevance
“…Several previous studies that analyzed the effect of inflation on stock prices (Alam et al, 2020;Antono et al, 2019;Begawati, 2017;Mulyanto & Riyanti, 2020;Šimáková et al, 2019;Utomo et al, 2019), inflation has a negative and significant effect on stock prices. In contrast to the research conducted (Bertuah & Sakti, 2019;Yusfiarto, 2020;Zuhroh, 2020), it states that inflation has a positive and significant effect on stock prices.…”
Section: 1contrasting
confidence: 59%
See 4 more Smart Citations
“…Several previous studies that analyzed the effect of inflation on stock prices (Alam et al, 2020;Antono et al, 2019;Begawati, 2017;Mulyanto & Riyanti, 2020;Šimáková et al, 2019;Utomo et al, 2019), inflation has a negative and significant effect on stock prices. In contrast to the research conducted (Bertuah & Sakti, 2019;Yusfiarto, 2020;Zuhroh, 2020), it states that inflation has a positive and significant effect on stock prices.…”
Section: 1contrasting
confidence: 59%
“…Several previous studies that analyzed the effect of inflation on stock prices (Alam et al, 2020;Begawati, 2017;Mulyanto & Riyanti, 2020) showed that inflation has a negative and significant effect on stock prices. In contrast to the research conducted (Sorcerer & Sakti, 2019;Zuhroh, 2020), it states that inflation has a positive and significant effect on stock prices. Another macroeconomic factor affecting stock prices is the exchange rate (Fakhruddin & Hadianto, 2016;Zuhroh, 2020) stated that the depreciation of the rupiah exchange rate can cause import costs to rise.…”
Section: Introductioncontrasting
confidence: 58%
See 3 more Smart Citations